2005
DOI: 10.1111/j.1398-9995.2005.00712.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between allergic rhinitis and hospital resource use among asthmatic children in Norway

Abstract: Concomitant allergic rhinitis in asthmatic children was associated with increased likelihood of asthma-related hospital readmissions and greater total hospital days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 18 publications
1
33
1
2
Order By: Relevance
“…Rhinitis as a risk factor for the control of asthma. Adults and children with asthma and documented concomitant allergic rhinitis experience more asthma-related hospitalizations and GP visits and incur higher asthma drug costs than adults with asthma alone (1909)(1910)(1911)(1912)(1913)(1914). These patients also experience more frequent absence from work and decreased productivity.…”
Section: Epidemiologic Links Between Rhinitis and Asthmamentioning
confidence: 99%
“…Rhinitis as a risk factor for the control of asthma. Adults and children with asthma and documented concomitant allergic rhinitis experience more asthma-related hospitalizations and GP visits and incur higher asthma drug costs than adults with asthma alone (1909)(1910)(1911)(1912)(1913)(1914). These patients also experience more frequent absence from work and decreased productivity.…”
Section: Epidemiologic Links Between Rhinitis and Asthmamentioning
confidence: 99%
“…During 1998-2001, a UK cohort study involving general practitioner medical records of 6-to 15-year-olds showed that 19.7 % of the asthmatic patients had AR [15]. Similarly, in the Norway National Database, 26.8 % of the children with at least one hospital admission for asthma, over a 2-year period, had a documented history of AR [16].…”
Section: Epidemiologic Evidencementioning
confidence: 99%
“…Studies regarding therapeutic aspects of AR and asthma indicate that treatments targeting either of them may alleviate the coexisting condition [16,32]. There are strong indications from observational data that treating co-morbid AR may result in better asthma outcomes in terms of asthma symptoms, emergency department visits and hospitalizations, and lower overall costs [33].…”
Section: Therapeutic Linkmentioning
confidence: 99%
“…Moreover, AR was predictive of a higher number of days of hospitalisation/year among asthmatics patients. 27 In addition, treatment of AR leads to improvements in asthma -as reported in studies observing a decrease in hospitalisation rates or emergency departments visits in patients with asthma and AR receiving intranasal corticosteroids. 28,29 The Global Initiative for Asthma (GINA) 30 recognises that AR is frequently associated with asthma and that AR needs to be treated in order to achieve good asthma control -in accordance with Allergic Rhinits and its Impact on Asthma recommendations.…”
Section: Discussionmentioning
confidence: 96%
“…Several studies suggest that improvement in asthma and AR control leads to a reduction in healthcare resource use; it has been demonstrated that untreated AR hinders asthma control, 24,25 and can lead to an increase in exacerbations and medication use. 26,27 Sazonov Kocevar et al followed 2,961 children with a history of hospitalisations for asthma and found that the risk of readmission among asthmatics with AR was 1.72 times higher than in asthmatics without AR. Moreover, AR was predictive of a higher number of days of hospitalisation/year among asthmatics patients.…”
Section: Discussionmentioning
confidence: 99%